engaruh Terpaan Pemberitaan Dompet Digital DANA dan Persepsi Komentar pada Akun Instagram @dana.id terhadap Minat Menggunakan Dompet Digital DANA - Yunisa Wirastanti, Tiara; Nur Suryanto Gono, Joyo; Surayya Ulfa, Nurist (Interaksi Online, 2024)
DANA, a digital wallet, is currently in the spotlight due to numerous negative reports and comments from its users. In 2023, DANA experienced a decline in the percentage of digital wallet usage in Indonesia. Several online news portals have also reported on the issues faced by DANA. Besides the online news portals, DANA users have expressed their concerns and posted negative reviews on every post made by the Instagram account @dana.id. Instagram and online news portals serve as platforms that can quickly disseminate information and provide spaces for discussion. The aim of this research is to determine the impact of negative news exposure on the digital wallet DANA and the perception of negative comments on the Instagram account @dana.id on the interest in using the digital wallet DANA. The theory used in this research is the Theory of Planned Behavior. This study employs a non-probability sampling technique with a population of 100 respondents, both male and female, who are social media users aged 18-34 years and have been exposed to negative news and have seen or read negative comments on the Instagram account @dana.id. The results of the research show that there is an negative influence between exposure to DANA news on interest in using the DANA digital wallet with a significance value of 0.000. Furthermore, the influence of the perception of comments on the @dana.id Instagram account on interest in using the DANA digital wallet has a significance value of 0.000. Therefore, it shows that there is an negative influence between the perception variable of comments on the @Dana.Id Instagram account on interest in using the DANA digital wallet